PARADIGM Workbook on Digital Private Papers - Libraries, B; Library, J (University of Oxford, 2019)
The Personal Archives Accessible in Digital Media (PARADIGM) project saw the major research libraries of the Universities of Oxford and Manchester come together to explore the issues involved in preserving digital private papers through gaining practical experience in accessioning and ingesting digital private papers into digital repositories, and processing these in line with archival and digital preservation requirements.